Parents' knowledge, attitude, and practice toward seasonal influenza vaccination of primary school children in Buraidah City, Qassim in 2018-2019 - Rahaf Khalid Alqarzai; Leen Majed Almaghyuli; Sharouq Ali Alolyan; Fai Mutlaq Alharbi; Ebtehal Khalid Aljehani; Dalia A Mohamed; Manal Mohamed Kamal (Wolters Kluwer Medknow Publications, 2022)
Introduction: Influenza viruses cause seasonal influenza which is an acute respiratory infection. The WHO reported that annually, there are about 290,000-650,000 deaths worldwide due to seasonal influenza. Vaccination is one of the most effective ways to prevent seasonal influenza and despite the high recommendation and the proven effectiveness of seasonal influenza vaccines in children, still, there is hesitancy and refuse among children's parents. Objective: This study assesses the parents' knowledge, attitude, and practice toward children's seasonal influenza vaccines (knowledge, attitude and practices). In addition, it aims to figures out solutions to increase awareness toward seasonal influenza vaccines. Methods: This study targets the parents of primary school children aged from 7 to 12 years who live in Buraidah. On 800 sample size, we used cluster random sampling. Self-administer hard copy questionnaire has been distributed. Results: The result shows that there is a significant association between the gender and receiving of flu vaccine P = 0.006, and the most common barrier prevents patents to vaccinate their children was because of their thoughts about its potential side effects 20.2%. Furthermore, there is no relationship between the educational level and the knowledge about seasonal influenza vaccination benefits P = 0.483614. In addition, a great proportion of our participants trust the information given to them by the Saudi Ministry of health and by their doctors 95.5% and 94.2%, respectively. Conclusions: We suggest increasing the effort in awareness campaigns and find a solution to correct the misconception and limits the rumors to increase the number of influenza vaccine uptake.